Potential Antidepressant Effects of Omeprazole Introduced Through Network Analysis and Systems Biology Should Be Interpreted with Caution in the Clinical Environment - Seyed-Ali Mostafavi (Iranian Journal of Psychiatry)
I am writing about an article published in the Iran J Psychiatry 2024; 19: 4: 367-383 titled "Identifying Key Genes and Approved Medications Associated with Major Depressive Disorder Using Network Analysis and Systems Biology" (1). The authors presented important findings about potential therapeutic candidates for Major Depressive Disorder (MDD) using Network Analysis and Systems Biology. One of the medications introduced as a candidate to have potential antidepressant effects was Omeprazole, based on its association with key genes identified in the pathogenesis of MDD. The authors have introduced the Omeprazole’s association with Tumor Necrosis Factor-α (TNF), and Interleukin-1β (IL-1 β) genes as the underlying mechanism for this proposal. Although I do appreciate the innovation with which the authors were able to use network analysis and systems biology to identify these potential relationships, I felt quite urged to present a more critical perspective before interpreting the findings of network analysis and systems biology into clinical practice.